Magneto-optics in transition metal diselenide monolayers. (10th June 2015) - Wang, G; Bouet, L; Glazov, M M; Amand, T; Ivchenko, E L; Palleau, E; Marie, X; Urbaszek, B
Abstract: We perform photoluminescence experiments at 4 K on two different transition metal diselenide monolayers (MLs), namely MoSe2 and WSe2 in magnetic fields B z up to 9 T applied perpendicular to the sample plane. In MoSe2 MLs the valley polarization of the neutral and the charged exciton (trion) can be tuned by the magnetic field, independent of the excitation laser polarization. In the investigated WSe2 ML sample the evolution of the trion valley polarization depends both on the applied magnetic field and the excitation laser helicity, while the neutral exciton valley polarization depends only on the latter. Remarkably, we observe a reversal of the sign of the trion polarization between WSe2 and MoSe2 . For both systems we observe a clear Zeeman splitting for the neutral exciton and the trion of about ±2 meV at T. The extracted Landé-factors for both exciton complexes in both materials are .